Silicon(IV) Derivatives of N-(o-Hydroxy Substituted Benzyl) Alanines - Shah, Ranjana; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several silicon (IV) derivatives of N-(o-hydroxy substituted benzyl) alanines have been prepared by the interaction of silicon tetraisopropoxide with the latter in appropriate stoichiometric ratios viz. 1 : 1, 1 : 2, 1 : 3, 1 : 4 and 2 : 3 in benzene medium. The compounds thus prepared were generally obtained as coloured solids out of which some were hygroscopic. All these compounds were characterized by elemental and azeotrope analyses, as well as by IR and PMR spectral measurements.